Karakteristik Ekonomi Pada Pengguna Ganda Rokok Elektrik dan Rokok Konvensional Pada Mahasiswa di Kota Bandung - Estro Dariatno Sihaloho, Herlina Silvani Purba Tambak (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
The number of electric cigarette users in Indonesia has increased significantly. They used electric cigarettes to stop used conventional cigarettes. In fact, users of electric cigarettes cannot reduce the use of conventional cigarettes. This study wants to see what factors cause university students in Bandung to use electronic cigarettes and conventional cigarettes together. This study uses primary data of 124 users of electric cigarettes and conventional cigarettes collected through surveys in the city of Bandung. This study uses the Logistic regression method with STATA 14. The results show that the allowance of students from parents, the status of other family members who smoke conventionally, how long they use conventional cigarettes, number of conventional cigarettes consumed per day before using electric cigarettes make university students be difficult to stop using conventional cigarettes after using electric cigarettes. The use of electric cigarettes and conventional cigarettes together will have a worse health impact. While the age and amount of e-cigarette expenditure reduces the possibility to consume e-cigarettes and conventional cigarettes together